Effect of lime and FYM on growth, yield and quality of soybean (Glycine max) grown in acid soils of Nagaland: Effect of lime and FYM on growth, yield and quality of soybean (Glycine max) grown in acid soils of Nagaland - A K SINGH; A O ENGRALA; AVINIE NAKHRO (Journal of Oilseeds Research, 2020)
The experiment was conducted during kharif season for three years to assess the impact of lime and FYM on soybean. Application of lime and FYM enhanced grain yield by 79% and 33%, respectively over control. Similar trend was observed with respect to haulm yield, oil content, protein content and nutrient NPK uptake.